2009
DOI: 10.2139/ssrn.1441844
|View full text |Cite
|
Sign up to set email alerts
|

Public Sector Employees: Risk Averse and Altruistic?

Abstract: We assess whether public sector employees have a stronger inclination to serve others and are more risk averse than employees in the private sector. A unique feature of our study is that we use revealed rather than stated preferences data. Respondents of a large-scale survey were offered a substantial reward and could choose between a widely redeemable gift certificate, a lottery ticket, or making a donation to a charity. Our analysis shows that public sector employees are significantly less likely to choose t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
3
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 34 publications
3
28
3
2
Order By: Relevance
“…Some scholars have characterized this agenda as an explicit attempt to alter the identity of the public sector worker (Horton 2006;Bourgault and Van Dorpe 2013). In particular, the relationship between trust and identification may be particularly important in understanding identification in the public sector, particularly as public servants may be more risk averse than their private sector counterparts (Buurman et al 2012) and are moreover accustomed to relatively stronger job security. Future studies that examine organizational identification across sectors and take into consideration these factors, therefore, may produce meaningful insights into identification processes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some scholars have characterized this agenda as an explicit attempt to alter the identity of the public sector worker (Horton 2006;Bourgault and Van Dorpe 2013). In particular, the relationship between trust and identification may be particularly important in understanding identification in the public sector, particularly as public servants may be more risk averse than their private sector counterparts (Buurman et al 2012) and are moreover accustomed to relatively stronger job security. Future studies that examine organizational identification across sectors and take into consideration these factors, therefore, may produce meaningful insights into identification processes.…”
Section: Resultsmentioning
confidence: 99%
“…The concept of organizational identification has as yet played little role in public administration scholarship, despite its obvious relevance to the field and the potential benefits that a deeper understanding how civil servants form a bond with their organization may deliver. In addition to having a strong identification with public sector values (Perry and Wise 1990), some evidence suggests that public sector workers may in general be more risk averse than their private sector counterparts (Buurman et al 2012), and as such organizational trust may be an important driver of identification in public organizations. Given this, using data from the public sector to explore how trust is related to organizational identification has both theoretical and practice-relevant advantages.…”
Section: Introductionmentioning
confidence: 99%
“…Support for the notion that incoming teachers tend to be relatively risk averse could have important implications for education policy-makers. Buurman et al (2012) note that if public employees are more risk averse, 'pay-for-performance is a more costly instrument to induce effort in the public sector than in the private sector' (4). Similarly, implementing performance pay may increase the levels of tension and worker dissatisfaction (Dohmen and Falk 2010;Perez 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Bellante and Link 1981;Hartog, Ferrer-i-Carbonell, and Jonker 2002;Masclet et al 2009). Taking advantage of a behavioural outcome measure, Buurman et al (2012) find that workers who have entered the public sector are less likely to choose riskier compensations for completing surveys than private sector employees. Dohmen and Falk (2010) have conducted a laboratory experiment with different payment schemes and found that those who self-reported being risk averse were more likely to prefer fixed wages.…”
Section: Risk Aversion and Existing Evidence On Teachers' Preferencesmentioning
confidence: 99%
“…(i) dictator games to examine how many resources an individual transfers to a pro-social task (Ashraf et al, 2014); and (ii) charitable contributions (Buurman et al, 2012).…”
mentioning
confidence: 99%